Creating a minority threat: Assessing the spillover effect of local immigrant detention on Hispanic arrests - Muchow, Ashley N. (Criminology, 2024)
Amid punitive shifts in crime and immigration control during the 1980s and 1990s, Hispanic individuals comprised a growing share of the population confined in U.S. prisons and jails. Although it is widely acknowledged that the nation's wars on crime and drugs contributed to higher rates of minority arrest, limited empirical research has examined whether the merging of immigration control with criminal justice practice during this period intensified these disparities. This article uses county-level arrest data from California between 1980 and 2004 to investigate whether intergovernmental service agreements (IGSAs) leasing jail space for immigrant detention increased rates of Hispanic arrest. Employing a quasi-experimental design that leverages the staggered adoption of IGSAs across counties, this study finds that these agreements increased rates of Hispanic arrest but had no discernible impact on arrest rates for White or Black residents. Supplemental analyses reveal that these increases were driven by misdemeanor arrests and were particularly pronounced in counties where the Hispanic population comprised between 11 and 22 percent. These findings suggest that IGSAs may trigger minority threat concerns that increase arrests, shedding additional light on Hispanic representation in the criminal justice system.